Ocena sytuacji finansowej zakładów ubezpieczeń na życie wybranymi metodami taksonomicznymi - Borda, Marta (Evaluation of Financial Standing of the Life Insurance Companies with Selected Taxonomic Methods, 2005)
In view of the specific nature of insurance activity, insurance companies more exposed to insolvency risk than other enterprises. From the insurer's point of view, the evaluation of the financial condition enables the identification and measurement of risk appearing in various areas of financial management. The paper presents an attempt of evaluation of financial standing of the life insurance companies operating in the Polish market between 1998 and 2002 using selected taxonomic methods. In order to achieve this aim ranking of the life insurers according to the synthetic development measure (TMKF) and classification of these institutions by application of k-means method and Ward's method were conducted.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 396-406